Current Disease pattern and Out-come of patients in a Medical Unit of a Pediatric Hospital - Rahman, M Mizanur; Islam, Mirza Md Ziaul; Islam, M Atiqul; Bhuiyan, AKM Tajuddin; Imran, AFM Ashik; Nahar, Mst Laizuman (Northern International Medical College Journal, 2020)
Background: Epidemiological trends of diseases and causes of mortality is not constant, it is always changing. Analysis of admitted patients gives us information on the burden of diseases in the community as well as cause of mortality. Objectives: To determine current pattern of admissions and their outcomes in a tertiary care Pediatric hospital. Material and Methods: A descriptive study was carried out at Dhaka Shishu (Children) Hospital over a period of one year from 1st January to 31st December, 2015. All the admitted patients during the study period were included and data were collected from medical records for analysis of age, residence, mode of admission, referral source, disease profile and outcome. Final diagnosis and mortality were grouped according to involved organ system. Data were analyzed by using SPSS version 17.0. Results: Total 1424children with a male and female ratio of 1.5:1 were admitted in one year. Patients younger than 5 years were 73%and 27% were less than one year. Respiratory infection, neurologic, hematology, oncologic conditions were the main diseases. Mortality was 2.6% and it was highest in nonspecific infection group followed by respiratory, hematologic, neurologic, and oncologic diseases. Mean duration of hospital stay was 11.5 days. Most patients 59.1% were admitted through Emergency Department(ED) and came directly to the hospital. Fifty percent of admissions were from Dhaka and neighboring areas and rest were from other cities and rural areas of Bangladesh. Conclusion: Non-specific infection, respiratory or neurologic diseases are main diseases found in admitted patients and these diseases were the main contributor to death as well. Most of the patients approach directly to this hospital and also through emergency department. Northern International Medical College Journal Vol.10 (2) Jan 2019: 386-388